Pelatihan Pemanfaatan Desmos untuk Pembelajaran Matematika bagi Peserta Didik Kelas X SMAN 1 Balen Bojonegoro - Mayasari, Novi; Junarti; Ali Noeruddin; Day Ramadhani Amir; Muh. Rinov Cuhanazriansyah; Lita Marga Ningrum (IKIP PGRI Bojonegoro, 2025)
ABSTRACT This community service activity aims to enhance students’ understanding of mathematical function graphs through the utilization of the Desmos application. The background of this program lies in the limited use of digital media in mathematics learning, which often causes difficulties for students in visualizing abstract concepts. The activity was carried out at SMAN 1 Balen Bojonegoro on November 27, 2025, involving 34 students and mathematics teachers. The implementation method included preparation, observation, training, mentoring, and evaluation. Participants were introduced to the features of Desmos and practiced creating function graphs interactively. The results showed an improvement in students’ understanding with an average N-Gain score of 0.41 (moderate category). Teachers also gained new insights into integrating technology into teaching. Overall, the training fostered more engaging and effective mathematics learning and strengthened the collaboration between IKIP PGRI Bojonegoro and SMAN 1 Balen. Keywords: Desmos, mathematics learning, function graphs, digital media, training ABSTRAK Kegiatan pengabdian kepada masyarakat ini bertujuan meningkatkan pemahaman siswa terhadap grafik fungsi matematika melalui pemanfaatan aplikasi Desmos. Latar belakang kegiatan ini adalah masih rendahnya penggunaan media digital dalam pembelajaran matematika yang menyebabkan siswa kesulitan memvisualisasikan konsep abstrak. Kegiatan dilaksanakan di SMAN 1 Balen Bojonegoro pada 27 November 2025 dengan melibatkan 34 siswa dan guru matematika. Metode pelaksanaan meliputi tahap persiapan, observasi, pelatihan, pendampingan, dan evaluasi. Peserta diperkenalkan fitur-fitur Desmos dan berlatih menggambar grafik fungsi secara interaktif. Hasil kegiatan menunjukkan peningkatan pemahaman siswa dengan nilai rata-rata N-Gain 0,41 (kategori sedang). Guru memperoleh wawasan baru mengenai integrasi teknologi dalam pembelajaran. Secara keseluruhan, pelatihan ini menjadikan pembelajaran matematika lebih menarik, efektif, dan memperkuat kerja sama antara IKIP PGRI Bojonegoro dan SMAN 1 Balen. Kata Kunci: Desmos, pembelajaran matematika, grafik fungsi, media digital, pelatihan